VOICES FROM THE LOCKER ROOM: A QUALITATIVE ANALYSIS OF VOICE MESSAGES WITHIN ITALIAN NSFW GROUPS. - Boccia Artieri, Giovanni; Brilli, Stefano; Zurovac, Elisabetta (AoIR Selected Papers of Internet Research, 2020)
The growing use of messaging apps group chats is defining a new geography of unsearchable digital conversations. Although these spaces often escape the range of internet research, because of the technical and ethical difficulties in extracting of large-scale data sets, they represent crucial contexts where new communication habits and cultural practices emerge. This paper aims to understand the use of voice messages in NSFW group chats, by looking at Telegram closed groups where pornographic contents are shared and commented. Since NSFW group chats are usually understood as prevalently anonymous contexts, the disclosure afforded by voices messages - particularly in terms of gender recognition - becomes worthy examining. More specifically, we ask: 1) What kind of interactions are enacted by voice messages? 2) What kind of self-disclosure is performed through voice messages? 3) Which challenges emerge in the moderation of voice messages? For this research, we are carrying out a qualitative content analysis of voice messages combined with in-depth interviews with groups’ moderators. Preliminary results suggest some circumstances that lead users to prefer using voice messages over text, gifs and static images. Contingent (not being able to text) or literacy-related reasons appear less important than the need to establish affective inclusion and identification through one’s own voice.